Hubungan Sosial Kemasyarakatan antara Ahl Al-Kitâb dan Muslim (Kajian Kitab Tafsîr al-Mannâr karya Muhammad Rasyid Ridha) - Mahmud Rifaannudin; Syamsul Hadi Untung (Universitas Darussalam Gontor, 2019)
“Ahl al-kitâb” in some opinions of theologian was term for Jews and Christians. In some opinions of theologian, they had been polytheistic and infidel, because they had denied the apostolate of the prophet Muhammad PBUH and the Holy Qur’an. However, Muhammad Rasyid Ridha in the interpretation of al-Manar argued that they were not polytheists. With different views of interpretation about the faith from ahl al- al-kitâb, certainly that will give rise to have implication for social relations with muslims, especially in the slaugter dish, marriage, and a leader. This research was compiled with documentation data collection method. Data that had been obtained and then analyzed with an interpretation science approach. Therefore, in this research it can be concluded that the form of social life interaction from ahl al- al-kitâb with muslims that was slaughter, marriage and make them become leaders. Thus, Muhammad Rasyid Ridha in al-Mannâr argues that ahl al-kitâb were not polystheists, but the mean of polytheists was Arab polytheism, because they did not have aposthes and scripture as a guide. therefore in the case of eating slaughter and marrying women, ahl al-kitâb allowed. However, Rasyid Rida give a forbided and rejected them become a leader.